Control of the bridge span vibration with high coefficient passive damper. Theoretical consideration and application. (1st March 2022) - Zoltowski, Krzysztof; Banas, Anna; Binczyk, Mikolaj; Kalitowski, Przemyslaw
Abstract: The research was carried out due to the problem of vibration on the lively pedestrian drawbridge across the Motlawa River in the city of Gdansk. In the design stage, the main span of the footbridge showed unfavorable dynamic properties, which may create a comfort problem for pedestrians. The first vertical bending eigenfrequency was recognized as 1.64 Hz. The original design of the footbridge was equipped with a driving cylinder to operate opening of the drawbridge. It was installed between the abutment and the pylon (integrated part of the span). Based on numerical calculations, it turned out that its high overdamping ratio can raise the value of the first vertical natural frequency to the level where pedestrian action has a low influence on the dynamic excitation of the span. It should be noted, the solution does not affect the behavior of the structure under static loads. Therefore, it was decided to modify the existing hydraulic driving cylinder to become a damper also. Analytical and numerical modeling was performed to establish an appropriate range of damper constant values. Finally, this idea was implemented in the structure. The theoretically defined effects of introducing a high ratio damper have been practically confirmed during the field test. The first vertical natural frequency of the span was shifted from 1.64 Hz to 3.1 Hz. The paper presents the work related to the solution of a specific case. However, the presented idea can be used in a wide spectrum of structures subjected to dynamic excitation. In practice, an external damper enables the change of a "static scheme" of the structure in the selected range of dynamic loads. This idea has a sense only in the case where response amplitude from dynamic loads is smaller than from the static action. Graphical abstract: Highlights: The use of a viscous damper can change a natural frequency. Driving hydraulic cylinders can be a damping device in drawbridge. Reduction of dynamic interaction of a footbridge and pedestrians. A high damper constant can reduce a damping ratio of a structure. A required damper constant can be determined based on a parametric dynamic analysis.